Blended Learning: Architectural Design Studio Experiences Using Housing in Istanbul - Yasemin Alkiser Bregger (Journal of Problem Based Learning in Higher Education, 2017)
This paper presents how a blended learning pedagogic model is integrated into an architectural design studio for housing in the Faculty of Architecture in Istanbul Technical University adapting the problem-based learning process. Fall 2015 and spring 2016 semester architectural design studios for fourth and sixth level undergraduate students in the ITU Faculty of Architecture were dedicated to housing issues. These studios collaborated with “Introduction to Housing” workspace in the EU OIKONET project. Integration of a blended learning pedagogic model into problem-based studio courses and its improvement in collaboration with the OIKONET platform over a year are also evaluated through the content of ITU design studios.